(untitled) (Journal of Partial Differential Equations, 2020)
With the aid of the nonhomogeneous Calderon-Zygmund decomposition the present paper studies the L^p estimates for a class of integral operators related to the boundary value problems of degenerate elliptic equations. The method used here is also applicable to general evolution equations of elliptic type.